Cultured Human Airway Epithelial Cells (Calu-3): A Model of Human Respiratory Function, Structure, and Inflammatory Responses - Yan Zhu; Aaron Chidekel; Thomas H. Shaffer (Critical Care Research and Practice)
This article reviews the application of the human airway Calu-3 cell line as a respiratory model for studying the effects of gas concentrations, exposure time, biophysical stress, and biological agents on human airway epithelial cells. Calu-3 cells are grown to confluence at an air-liquid interface on permeable supports. To model human respiratory conditions and treatment modalities, monolayers are placed in an environmental chamber, and exposed to specific levels of oxygen or other therapeutic modalities such as positive pressure and medications to assess the effect of interventions on inflammatory mediators, immunologic proteins, and antibacterial outcomes. Monolayer integrity and permeability and cell histology and viability also measure cellular response to therapeutic interventions. Calu-3 cells exposed to graded oxygen concentrations demonstrate cell dysfunction and inflammation in a dose-dependent manner. Modeling positive airway pressure reveals that pressure may exert a greater injurious effect and cytokine response than oxygen. In experiments with pharmacological agents, Lucinactant is protective of Calu-3 cells compared with Beractant and control, and perfluorocarbons also protect against hyperoxia-induced airway epithelial cell injury. The Calu-3 cell preparation is a sensitive and efficient preclinical model to study human respiratory processes and diseases related to oxygen- and ventilator-induced lung injury.